‘We Come as Doctors, We Come as Servants’ Medical Confidentiality and Professional Identity during the Great War - Jacobs, Noortje (Studium, 2014)
This article explores discussions in the Nederlandsch Tijdschrift voor Geneeskunde (NTvG), the Dutch Journal of Medicine, over the limits of medical confidentiality during the First World War. In the early twentieth century, physicians in the Netherlands struggled with the socio-legal limits of the ‘physician’s oath’ (i.e. ‘artseneed’), the vow of secrecy sworn by Dutch medical doctors since 1878 at Dutch universities upon the acceptance of their profession. While the 1865 codification of medical confidentiality in the Netherlands had significantly contributed to the socio-legal status of the profession vis-à-vis ‘quacks’, it became clear in the late nineteenth and early twentieth century that the traditional ideal of the secret absolu did not fit well with the growth of modern state structures. With the development of elaborate bureaucratic institutions and the subsequent need for population statistics and formalized accountability mechanisms, Dutch physicians were asked more and more often to provide information which had traditionally fallen within the realm of medical confidentiality to third parties. This article examines this ‘dilemma of modernity’ by looking into discussions in the NTvG over the respective identities of military and civilian physicians between 1914 and 1918, and argues that, during the war years, the professional identity of the health officer – with his explicit double function as doctor and as servant – came to function as a projection screen for civilian physicians in the Netherlands to debate existing anxieties regarding their role in the modern Dutch state.